2010
DOI: 10.1111/j.1440-1681.2010.05432.x
|View full text |Cite
|
Sign up to set email alerts
|

Coronary vascular dysfunction promoted by oxidative‐nitrative stress in SHRSP.Z‐Leprfa/IzmDmcr rats with metabolic syndrome

Abstract: 1. Metabolic syndrome is an independent risk factor for cardiovascular disease. SHRSP.Z-Lepr(fa) /IzmDmcr (SHRSP fatty) rat, established as a new rat model of metabolic syndrome, spontaneously develops obesity, severe hypertension and shows hypertriglyceridaemia, hypercholesterolaemia and abnormal glucose tolerance. Using SHRSP fatty rats, we examined whether or not oxidative stress was correlated with vascular dysfunction in small and large calibre coronary arteries in ex vivo beating hearts, isolated mesente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 46 publications
1
20
1
Order By: Relevance
“…10,25,26) We reported that impairment of coronary microcirculation associated with activation of angiotensin type I receptor occurred in SHRSP-fatty. 8) In the present study, we found that collagen type I accumulated in the ventricles along with diastolic dysfunction in SHRSPfatty. Collagen type I confers rigidity while collagen type III contributes to tissue elasticity, and an increase in the ratio of collagen type I to type III is known to be associated with increased myocardial stiffness in hypertensive rats with diastolic heart failure.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…10,25,26) We reported that impairment of coronary microcirculation associated with activation of angiotensin type I receptor occurred in SHRSP-fatty. 8) In the present study, we found that collagen type I accumulated in the ventricles along with diastolic dysfunction in SHRSPfatty. Collagen type I confers rigidity while collagen type III contributes to tissue elasticity, and an increase in the ratio of collagen type I to type III is known to be associated with increased myocardial stiffness in hypertensive rats with diastolic heart failure.…”
Section: Discussionmentioning
confidence: 52%
“…In previous studies we have proposed that peroxynitrite played a critical role in development of cardiovascular events in SHRSP-fatty. 8,[34][35][36][37] Additional studies are needed to be clarified involvement of MMPs, MLC-1 and peroxynitrite in progression of ventricular diastolic dysfunction in SHRSPfatty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aortic rings were prepared for myograph experiments as described previously [10]. For each aortic ring, a stable level of isometric contraction was established by addition of phenylephrine (0.1 µ M ) before measuring relaxations following the addition of increasing cumulative concentrations (final bath concentrations) of PAR2 agonist 2-furoyl- LIGRLO-amide (2fly; 0.1 n M -3 μ M ) [21], muscarinic agonist acetylcholine (ACh; 0.1 n M -3 μ M ) or nitrovasodilator sodium nitroprusside (SNP; 0.1 n M -1 μ M ).…”
Section: Methodsmentioning
confidence: 99%
“…In this model, coronary and mesenteric arteries and aortas show vascular dysfunction that is characterized by impaired NO-cGMP-dependent vasodilation resulting from decreased soluble guanylate cyclase (sGC) expression [10,11]. However, even under these conditions, PAR2-mediated vasodilation is preserved in mesenteric arteries from SHRSP.ZF [12].…”
Section: Introductionmentioning
confidence: 99%